Removal of decaying DC in current and voltage signals using a modified Fourier filter algorithm. - Sun-Li Yu
Protecting transmission lines frequently involves applying distance relays. Protective relays must filter their inputs to reject unwanted quantities and retain signal quantities of relevant interest. Accuracy and convergent speed of filter algorithm are essential for protective relays. A widely applied filter algorithm, the discrete Fourier transform (DFT) can easily remove integer harmonics using simple calculation. However, the voltage and current signals contain serious harmonics and decaying DC during the fault interval. In addition, the decaying DC and higher order harmonics seriously decrease the precision and convergence speed of fundamental frequency signal from DFT. In this investigation, the authors derive a novel algorithm which combines the appropriate analog low pass filter and modified full cycle DFT (FCDFT) or half cycle DFT (HCDFT) algorithm to remove the decaying dc in a voltage or current signal. Using the Electromagnetic Transients Program (EMTP) simulates the transient responses of transmission lines during the fault period. Applying the proposed algorithm in distance relays effectively suppresses the decaying DC and quickly decomposes the accurate fundamental frequency components
Keywords: DC current decay; EMTP; Electromagnetic Transients Program; Current signals; Discrete Fourier transform; Distance relays; Filter algorithm; Fundamental frequency components; Higher order harmonics; Integer harmonics; Low pass filter; Modified Fourier filter algorithm; Power transmission line protection; Transient response; Voltage signals